Synthesis of Luminescent Polystyrene with p-Conjugated Pendant - Wang, Feng; Zhu, Cai-Xia (Asian Journal of Chemistry, 2013)
One novel polystyrene-based copolymer (PS-PF) with p-conjugated unit (fluorneyl and phenyl rings) as pendant was designed and synthesized using radical polymerization method and initiated by AIBN (2,2'-azobisisobutyronitrile) from the new functional monomer, which contained the conjugated unit and reactive double bond. Nuclear magnetic resonance, FT-IR and UV-visible spectra were used to characterize the structure of intermediate and copolymer. The PS-PF is easily dissolved in organic solvent such as THF and CH3Cl and to be formed thin film by spin coating. The ink-jet printing method was applied to form blue pattern. The strongest emission of the as prepared copolymer was at 416 nm with shoulder peak of 441 nm in the solution and 440 nm with shoulder peak in the film state.